NIKAH DALAM AL-QUR’AN - Rusdaya, Rusdaya (DIKTUM: Jurnal Syariah dan Hukum, 2016)
The focus of this discussion is the concept and purpose of marriage as well as a description of the women were forbidden to marry according to the Koran. Based on the verses of the Koran to understand that marriage is a covenant between the male and female party to officially married wives, in addition klins majazi- he also interpreted as sexual intercourse. When it comes to marriage, the Qur'an uses two terms, namely marriage and zawj. It's just that the word marriage is more geared towards use in humans Keberpasangan with each other, while zawj has a more general meaning. While women were not allowed to marry by a few verses, the scholars of fiqh classifying pengharamannya on two reasons, namely; because that is eternal or forever (al-muharramat al-muabbadah), and cause temporary (al-muharramat al-muaqqatah).